The Archaeology of Mediterranean Prehistory. - Blake, Emma (Blackwell studies in global archaeology, 2007)
This book offers a comprehensive introduction to the archaeology of Mediterranean prehistory. Its case studies, spanning the Neolithic through the Iron Age, are drawn from all the Mediterranean's major lands, coasts, and islands. Written by fourteen of the leading archaeologists in the field, The Archaeology of Mediterranean Prehistory presents diverse theoretical approaches that enable students as well as other archaeologists to see the benefits of multivocality.